2020
DOI: 10.3233/sji-200741
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of disaggregated SDG indicators with cluster information for small area estimates

Abstract: The increasing needs for more disaggregated data motivates National Statistical Offices (NSOs) to develop efficient methods for producing official statistics without compromising on quality. In Indonesia, regional autonomy requires that Sustainable Development Goals (SDGs) indicators are available up to the district level. However, several surveys such as the Indonesian Demographic and Health Survey produce estimates up to the provincial level only. This generates gaps in support for district level policies. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Cluster information can be incorporated into the SAE area-level models either as a categorical variable [66] or as an additional parameter to improve the estimates' efficiency [67,68]. In some studies, employing hierarchical clustering based on covariates has been shown to effectively yield more accurate predictions of small area means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster information can be incorporated into the SAE area-level models either as a categorical variable [66] or as an additional parameter to improve the estimates' efficiency [67,68]. In some studies, employing hierarchical clustering based on covariates has been shown to effectively yield more accurate predictions of small area means.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by considering whether variance components are equal or unequal across different clusters [69]. Lastly, cluster information can be included as an average area random effects value in both unit-level [70] and area-level models [68,71,72] for predicting non-sampled areas.…”
Section: Discussionmentioning
confidence: 99%
“…Topic 2 highlights the new skills in statistics needed to handle big data, which implies the emergence of the Data Science field and the importance of democratising the data understanding. In addition, the topic also highlights the Sustainable Development Goals (SDGs) in the context of the data revolution, and an example of this is "Improving the quality of disaggregated SDG indicators with cluster information for small area estimates" by Zulkarnain et al [8]. Topic 3 focuses on data management, such as data acquisition and integration.…”
Section: The Data Revolution and Official Statisticsmentioning
confidence: 99%
“…The process for getting data from alternative online sources consists in "web scraping" 7 the information by following these steps: 1) searching for information on the internet, mainly from National Statistical Offices or Ministries websites; 8 2) extracting the data from its original source (e.g., PDF documents, Microsoft Excel files) and transforming it to a common format (a SQL table); 3) standardising the data, with respect to commodity names (converted to the Central Product Classification, CPC 9 ) and administrative area names (converted to GADM 10 ); 4) comparing to FAOSTAT data; 5) saving consistent data to the agricultural production database or analysing discrepancies. Though this process seems relatively straightforward, it is indeed plagued with several difficulties.…”
Section: Using "Web Scraped" Information For Agricultural Statisticsmentioning
confidence: 99%
See 1 more Smart Citation